2010
DOI: 10.1186/1752-1947-4-175
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lobular carcinoma of the breast presenting as retroperitoneal fibrosis: a case report

Abstract: IntroductionInvasive lobular carcinoma of the breast represents approximately 6.3% of mammary malignancies. Distant metastasis of invasive lobular carcinoma to the peritoneum or retroperitoneum has been reported fairly frequently.Case presentationWe report the case of a 59-year-old Caucasian-Canadian woman with invasive lobular carcinoma of the breast presenting with retroperitoneal fibrosis and bilateral ureteral obstruction. Intra-operative pathology consultation did not reveal malignancy. The diagnosis, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The interval time from first diagnosis and recurrence varies from a few months to years and synchronous presentation is an extremely rare event [7,9,12]. Rarer is to find such kind of metastases in the absence of known or clinically evident primary breast cancer [6][7][8][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval time from first diagnosis and recurrence varies from a few months to years and synchronous presentation is an extremely rare event [7,9,12]. Rarer is to find such kind of metastases in the absence of known or clinically evident primary breast cancer [6][7][8][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Rarer is to find such kind of metastases in the absence of known or clinically evident primary breast cancer [6][7][8][9][10][11][12]. Two cases of intra-abdominal metastasis from occult breast cancer are described here, in two patients admitted to our Surgery Department for complaints of jaundice and rectal bleeding, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…Often, the condition is associated with other autoimmune conditions, especially those that fall into the category of IgG4-related sclerosing diseases [2]. In contrast, secondary RF seems to affect a broader age of patients and has been linked to several conditions including drug reactions, malignancy, infection, radiation therapy, surgical changes, and amyloidosis [1,4,5].…”
Section: Discussionmentioning
confidence: 95%
“…Distant metastases in the retroperitoneum, gastrointestinal tracts, leptomeninges, orbit and genitourinary tract have been reported more frequently in ILC. 7 Most cases of breast cancer metastasising to the urinary tract are detected as a part of disseminated disease either during follow-up or at autopsy. A review of autopsies in 181 cases of metastatic breast cancer showed ureteral involvement in 8.3% of cases.…”
Section: Discussionmentioning
confidence: 99%